2017
DOI: 10.3892/ijmm.2017.3220
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide DNA methylome alterations in acute coronary syndrome

Abstract: Acute coronary syndrome (ACS) is a common disease with high mortality and morbidity rates. The methylation status of blood DNA may serve as a potential early diagnosis and prevention biomarker for numerous diseases. The present study was designed to explore novel genome-wide aberrant DNA methylation patterns associated with ACS. The Infinium HumanMethylation450 assay was used to examine genome-wide DNA methylation profiles in 3 pairs of ACS and control group samples. Epigenome-wide DNA methylation, genomic dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 59 publications
(49 reference statements)
0
10
0
Order By: Relevance
“…PYROXD1 is involved in the response to oxidative stress [ 27 ]. Recent studies report higher DNAm in this gene in acute coronary syndrome and brain white matter lesions in older populations [ 28 , 29 ]. Furthermore, a microarray-based post mortem analysis in human dorsal raphe nucleus tissue, a brain region pathophysiologically involved in serotonergic neurotransmission in MDD, showed a significant upregulation of the PYROXD1 transcript in MDD cases vs. controls, corresponding to higher protein production related to MDD [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…PYROXD1 is involved in the response to oxidative stress [ 27 ]. Recent studies report higher DNAm in this gene in acute coronary syndrome and brain white matter lesions in older populations [ 28 , 29 ]. Furthermore, a microarray-based post mortem analysis in human dorsal raphe nucleus tissue, a brain region pathophysiologically involved in serotonergic neurotransmission in MDD, showed a significant upregulation of the PYROXD1 transcript in MDD cases vs. controls, corresponding to higher protein production related to MDD [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…In recent year, studies focusing on the relationship between epigenetics and CAD revealed that aberrant methylation of gene promoter might be implied in the etiology of CAD [6, 22]. As an important component of complement system, C3 may be involved in the occurrence and development of CAD by direct and indirect mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…In the study of genome-wide methylation in ACS, 19 hypermethylated loci and 17 hypomethylated genes that may be markers of ACS were identified, however, the association of methylation with nosology in the case-control study using methyl-specific PCR was confirmed only for the SMAD3 locus [55]. Another epigenome-wide study using the whole blood of 102 patients with ACS and 101 people in the control group identified 47 CpG sites associated with ACS.…”
Section: Dna Methylation and Ischemic Heart Diseasementioning
confidence: 99%